The Urgency of Accountant In Disruption Era - Nadilla, Trie (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
Disruption of digital technology is an era of fundamental innovation and massive change due to the presence of digital technology, changing systems that occur in Indonesia and globally. The development of digital technology is able to replace human work. Accountants are a profession that developed from century to century and has experienced ups and downs in maintaining existence. This profession is growing become a trust-creating business society and expect it as a profession that promising. Recently, in the digital era and technological developments, the flow of information goes like that fast, internet technology has changed a person's view of obtaining information, including in the world of business accounting. This research is descriptive research. The conclusion is an must have hardskill and softskill. Hardskill such as up to date technology expertise, communication skills, have certification, understanding using software accounting, invest developing digital skills. Softskill consist of critical thingking ability, creativity and willingness to help others, customer service orientation.